Therapeutic effect of psilocybin in addiction: A systematic review - van der Meer, Pim B.; Fuentes, Juan J.; Kaptein, Ad A.; Schoones, Jan W.; de Waal, Marleen M.; Goudriaan, Anneke E.; Kramers, Kees; Schellekens, Arnt; Somers, Metten; Bossong, Matthijs G.; Batalla, Albert (Frontiers in Psychiatry, 2023)
Background Psychedelic-assisted therapy (e.g., with lysergic acid diethylamide [LSD]) has shown promising results as treatment for SUDs. Previous systematic reviews evaluating the efficacy of psilocybin in SUDs only included clinical trials conducted in the last 25 years, but they may have missed clinical trials evaluating the efficacy of psilocybin that were conducted before the 1980s given much research has been done with psychedelics in the mid-20th century. In this systematic review, we specifically assessed the efficacy of psilocybin in patients with a SUD or non-substance-related disorder with no publication date restrictions in our search strategy. Methods A systematic literature search was performed up to September 2, 2022, in 7 electronic databases including clinical trials in patients with a SUD or non-substance-related disorder evaluating the efficacy of psilocybin. Results A total of 4 studies (6 articles, of which 2 articles were long-term follow-up results from the same trial), were included in this systematic review. Psilocybin-assisted therapy was administered to n=151 patients in a dose ranging from 6 to 40mg. Three studies focused on alcohol use disorder and one study on tobacco use disorder. In a pilot study (n=10), the percentage in heavy drinking days decreased significantly between baseline and weeks 5-12 (mean difference of 26.0%, 95%CI=8.7-43.2, p=0.008). In another single-arm study (n=31), 32% (10/31) became completely abstinent from alcohol (mean duration of follow-up 6 years). In a double-blind, placebo-controlled randomized controlled trial (RCT, n=95), the percentage of heavy drinking days during the 32-week double-blind period was significantly lower for psilocybin compared to placebo (mean difference of 13.9%, 95%CI=3.0-24.7, p=0.01). In a pilot study (n=15), the seven-day point prevalence smoking abstinence at 26 weeks was 80% (12/15) and at 52 weeks 67% (10/15). Conclusion Only one randomized controlled trial and three small clinical trials were identified evaluating the efficacy of psilocybin combined with some form of psychotherapy in patients with alcohol and tobacco use disorder. All four clinical trials indicated a beneficial effect of psilocybin-assisted therapy on SUD symptoms. Larger RCTs in patients with SUDs need to evaluate whether psilocybin-assisted therapy is an effective treatment in patients with SUD.